1994
DOI: 10.1103/physrevlett.72.4121
|View full text |Cite
|
Sign up to set email alerts
|

Linear Temperature Dependent Resistivity at Constant Volume inRb3C60

Abstract: The normal-state electrical resistivity p of the superconductor Rb3C60 has been measured as a function of temperature and hydrostatic pressure. Under conditions of constant sample volume we find a linear temperature dependence, p -T, in sharp contrast to p -T observed under conditions of constant sample pressure. The pressure dependence of p at fixed temperature is exponential, with a reduction in p by more than 50% for 8 kbar at room temperature. Implications for the normal-state scattering mechanism are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 17 publications
6
22
0
Order By: Relevance
“…Actually, the corrected data show signs of saturation. A similar correction of the data for Rb 3 C 60 (Vareka and Zettl, 1994) changed the approximately quadratic T dependence found for constant pressure (see Fig. 3) to an approximately linear dependence for constant volume.…”
Section: Resultsmentioning
confidence: 93%
“…Actually, the corrected data show signs of saturation. A similar correction of the data for Rb 3 C 60 (Vareka and Zettl, 1994) changed the approximately quadratic T dependence found for constant pressure (see Fig. 3) to an approximately linear dependence for constant volume.…”
Section: Resultsmentioning
confidence: 93%
“…Experiments show that for a wide range of temperatures T the resistivity depends linearly on T, particularly in Á3C60 (cf. [5]), which cannot be attributed to scattering on classical phonons. For the same reason status of superconductivity phonon mechanism is unclear in these crystals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we focus on this mechanism below. More recent experimental work (Vareka and Zettl, 1994) has suggested that ρ(T ) at constant volume is linear in T down to relatively low T (100-200 K). This raises new questions, and the resistivity can not be considered as fully understood.…”
Section: Resistivitymentioning
confidence: 99%
“…9 are for constant pressure. The experimental data have also been converted to constant volume, by measuring the pressure dependence (Vareka and Zettl, 1994). The resistivity then shows an approximately linear behavior for temperatures larger than about 100 to 200 K. This linear behavior appears not to have been explained theoretically, and it is an interesting problem.…”
Section: Resistivitymentioning
confidence: 99%